2020
DOI: 10.1140/epjc/s10052-020-7663-x
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement dynamics for static two-level atoms in cosmic string spacetime

Abstract: We study the entanglement dynamics of two static atoms coupled with a bath of fluctuating scalar fields in vacuum in the cosmic string spacetime. Three different alignments of atoms, i.e. parallel, vertical, and symmetric alignments with respect to the cosmic string are considered. We focus on how entanglement degradation and generation are influenced by the cosmic string, and find that they are crucially dependent on the atom-string distance r , the interatomic separation L, and the parameter ν that character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This unique structure also influences quantum fluctuations of fields, which results in significant modifications to several quantum phenomena. Notable effects include alterations to the Casimir-Polder effect [36,37], atomic transitions [38][39][40][41], resonance interactions [42], fluctuations of the lightcone [43], and the dynamics of entanglement [44]. Noteworthily, there has been a proposal for the experimental detection of analogous spacetime metric fluctuations through the observable variance in flight time near fabricated analog cosmic strings, as detailed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…This unique structure also influences quantum fluctuations of fields, which results in significant modifications to several quantum phenomena. Notable effects include alterations to the Casimir-Polder effect [36,37], atomic transitions [38][39][40][41], resonance interactions [42], fluctuations of the lightcone [43], and the dynamics of entanglement [44]. Noteworthily, there has been a proposal for the experimental detection of analogous spacetime metric fluctuations through the observable variance in flight time near fabricated analog cosmic strings, as detailed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, quantum entanglement has been analysed through the lens of the relativistic quantum information theory, which studies the behaviour of atoms interacting with relativistic quantum fields [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. A well known phenomenon in this scenario is the so-called entanglement degradation, when correlated states become uncorrelated by the interaction with a quantum field [57][58][59][60][61]. Another effect is the entanglement harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a "global conical deficit" on the vacua of quantum fields have been studied in the literature, such as the vacuum polarisation of the field [18][19][20] and particle creation in these spacetimes [21,22]. UDW detectors and other quantum particles in cosmic string spacetimes have also been studied in the literature and it has been demonstrated that the detectors or particles are in general sensitive to the presence of a cosmic string [23][24][25][26][27][28][29][30]. Contrary to all these studies, in our setup the UDW detector is not situated in the region with the conical deficit and such a deficit is only present outside the cylinder.…”
Section: Introductionmentioning
confidence: 99%